Evaluation of the Support Structure Removal Techniques for Additively Manufactured Ti6AL4V Parts - Wadea Ameen; Abdulrahman Al-Ahmari; Muneer Khan Mohammed; Osama Abdulhameed (Advances in Materials Science and Engineering)
Support structures are required for overhanging surfaces in additive manufacturing to prevent part deformation. However, these support structures are undesirable because they are removed during postprocessing after the part is built. It is critical to remove metal support structures because they can occasionally leave residue on the part. Among the various support-removal techniques, manual removal and wire electrical discharge machining (EDM) are the most frequently used. While most manufacturers recommend the manual method due to its economic benefits, it may be challenging for thin walls, small-scale components, and brittle materials. The purpose of this study is to evaluate and compare these two methods, taking into account both their advantages and disadvantages. The results indicate that while manual support-removal is quick, it results in a degraded surface topography and increased surface roughness due to support tooth remnants and residue. The wire EDM method of removing support resulted in a more uniform surface topography and a superior surface finish. However, as a result of thermal damage, a heat-affected zone developed on the machined surface.